Illness Perception in Adolescent Patients With Anorexia: Does It Play a Role in socio-Emotional and Academic Adjustment? - Quiles, Yolanda; Quiles, Maria José; León, Eva; Manchón, Javier (Frontiers in Psychology, 2020)
People’s beliefs about their illness have been shown to affect their adjustment. The aim of this study was to describe illness perception in adolescent patients with anorexia nervosa and assess its relationship with socio-emotional and academic adjustment following Leventhal’s Self-Regulation Model. Thirty-four female anorexia nervosa patients, with a mean age of 15.76 (SD = 2.00), completed the Revised Illness Perception Questionnaire (IPQ-R), the Psychosocial Adjustment to Illness Scale (PAIS) and the Hospital Anxiety and Depression Scale (HAD). Adolescent anorexia patients perceived that they had control over their illness and treatment would improve their condition. However, they also believed that it was highly distressing, going to last a long time and would have serious consequences. As for the causes of the disorder, they were attributed primarily to a specific eating disorder and psychological factors. The results showed that anorexia patients’ illness perceptions were related to socio-emotional and academic adjustment. In this sense, identity with the illness was associated with a worse academic adjustment, while emotional representation was associated with a worse emotional and social adjustment. These findings highlight how important it is for patients’ beliefs about their disease to be considered in the treatment of anorexia. In this respect, clinicians treating these patients should consider how certain beliefs affect their academic and socio-emotional adjustment. It would be interesting for patients to become aware of how these beliefs influence the strategies they use to cope with their disease as well as their adjustment to it.